Self-compassion scale (SCS): initial psychometric evidence in Lima teens - Ardela Cabrera, Christian (2019)
An instrumental design study was conducted with the aim of analyzing the psychometric evidence of the Compassion Scale (SCS) in high school students from Los Olivos, Lima. The sample consisted of 260 adolescents. Evidence of content validity was obtained by statistical analysis of items, also with the judgment of 10 experts based on Aiken’s V. and binomial test. Exploratory factorial analysis was performed: KMO = .79, significant Bartlett test (p < .001), variance = 32 %. The confirmatory factor analysis showed the best fit of the model of six factors: IFC = .91, SRMR = .056 and RMSEA = .038. In addition, an acceptable internal consistency was found based on the total score and dimensions, except for the shared humanity dimension. In relation to the validity of criteria, a statistically significant and positive correlation of self-compassion with satisfaction with life and resilience is evident. Finally, standards of interpretation were developed at levels: low, medium and high. In short, the Scale (SCS) gathers sufficient evidence of validity and reliability for its application in adolescents.